Odpowiedzi

2009-11-18T20:55:31+01:00
F(x)=3x-2
3x-2=0
x=2/3
f(X)=pierwiastek z x-4 pierwiastek z x=4
jesli f(x)=pierwiastek z (x-4)
pierwiastek z x-4 =0
x-4=0
x=4
jesli
f(X)=pierwiastek z x-4 pierwiastek z x+4=-3√x+4
-3√x+4=0
-3√x=-4
√x=4/3
x=16/9

f(x)=5/2x
5/2x=0
x=0

jesli mialo byc
5/(2x)=0
brak miejsca zer

f(x)=x do2-9
x²-9=0
(x-3)(x+3)=0
x=3 v x=-3

f(x)=1/2+1/3
tu brak
2009-11-18T21:00:06+01:00
0=3x-2
3x=2
x=2/3

f(X)=pierwiastek z x-4 pierwiastek z x=4

0=5/2x
x=0

0=x2-9
x2=9
x=√9
x=3

0=1/2+1/3
-1/3 nie równa się 1/3 ?

Czy to jest dobrze przepisane wszystko?
2009-11-18T20:59:45+01:00
F(x)=3x-2
3x-2=0
x=2/3
f(X)=pierwiastek z x-4 pierwiastek z x=4
jesli f(x)=pierwiastek z (x-4)
pierwiastek z x-4 =0
x-4=0
x=4
jesli
f(X)=pierwiastek z x-4 pierwiastek z x+4=-3√x+4
-3√x+4=0
-3√x=-4
√x=4/3
x=16/9

f(x)=5/2x
5/2x=0
x=0